Effective Synthesis of Silicon Carbide Nanotubes by Microwave Heating of Blended Silicon Dioxide and Multi-Walled Carbon Nanotube - Tony,Voo Chung Sung (2017)
Silicon carbide nanotube (SiCNTs) has been proven as a suitable material for wide applications in high power, elevated temperature and harsh environment. For the first time, we reported in this article an effective synthesis of SiCNTs by microwave heating of SiO2 and MWCNTs in molar ratio of 1:1, 1:3, 1:5 and 1:7. Blend of SiO2 and MWCNTs in the molar ratio of 1:3 was proven to be the most suitable for the high yield synthesis of β-SiCNTs as confirmed by X-ray diffraction pattern. Only SiCNTs were observed from the blend of MWCNTs and SiO2 in the molar ratio of 1:3 from field emission scanning electron microscopy imaging. High magnification transmission electron microscopy showed that tubular structure of MWCNT was preserved with the inter-planar spacing of 0.25 nm. Absorption bands of Si-C bond were detected at 803 cm-1 in Fourier transform infrared spectrum. Thermal gravimetric analysis revealed that SiCNTs from ratio of 1:3 showed the lowest weight loss. Thus, our synthetic process indicates high yield conversion of SiO2 and MWCNTs to SiCNTs was achieved for blend of SiO2 and MWCNTs in molar ratio of 1:3.